Synthesis of PMMA-b-PU-b-PMMA tri-block copolymers through ARGET ATRP in the presence of air - P. Krol; P. Chmielarz (eXPRESS Polymer Letters)
ARGET (activators regenerated by electron transfer) ATRP (atom transfer radical polymerization) has been successfully performed (in flasks fitted with rubber septa without the need for use of Schlenk line) in the presence of limited amount of air and with a very small (370 ppm) amount of copper catalyst together with an appropriate reducing agent Cu(0). Novelty of this work is that the poly(methyl methacrylate)-block-polyurethane-block-poly(methyl methacrylate) triblock copolymers were synthesized for the first time through ARGET ATRP, by using tertiary bromine-terminated polyurethane as a macroinitiator (MBP-PU-MBP), CuBr2 or CuCl2 as a catalyst and N,N,N',N",N"-pentamethyldiethylenetriamine (PMDETA) or 2,2'-bipyridine (Bpy) as a complexing agent. As the polymerization time increases, both the monomer conversion and ln([M]0/[M]) increased and the molecular weight of copolymer increases linearly with increasing conversion. Theoretical number-average molecular weight (Mn, th) of the tri-block copolymers was found to be comparable with number-average molecular weight determined by GPC analyses (Mn, GPC). These results indicate that the formation of the tri-block copolymers was through atom transfer radical polymerization mechanism. 1H and 13C NMR spectral methods were employed to confirm chemical structures of synthesized macroinitiator and tri-block copolymers. Mole percentage of PMMA in the tri-block copolymers was calculated using 1H NMR spectroscopy and was found to be comparable with the GPC results. Additionally, the studies of surface properties (confocal microscopy and SFE) of tri-block copolymer coatings confirmed the presence of MMA segments.